Impact of Treatment on Rate of Biphasic Reaction in Children with Anaphylaxis - William Bonadio; Connor Welsh; Brad Pradarelli; Yunfai Ng (Western Journal of Emergency Medicine)
Objective: Our goal was to characterize a large group of children presenting to the emergency department (ED) with acute anaphylaxis, treated with intramuscular epinephrine (IM EPI) and a corticosteroid (CS), and to determine the impact of pharmacologic intervention on the rate and timing of biphasic reactions (BPR). Methods: We reviewed consecutive children diagnosed with acute anaphylaxis managed in three EDs during a six-year period. All received IM EPI and CS, followed by monitoring for 4–6 hours post-treatment. We analyzed the rate and timing of BPR, comparing the intervals of 0–4 vs 4–48 hours after initiating therapy. Results: During the study period, there were 371 cases of anaphylaxis, of which 357 (94%) received both IM EPI and CS. Of these, 49 (14%) manifested BPR [84% had received prehospital IM EPI] requiring at least one additional dose of IM EPI [14% required ≥2 additional doses]. All BPR episodes occurred within the 0–4 hour interval after initiating therapy, whereas no patient manifested a BPR requiring an additional dose of IM EPI during the 4–48 hours after initiating therapy (P = <0.001, 95% CI 0–1.3%). No patient returned to the ED with recurrence of anaphylaxis symptoms within 48 hours after discharge. Conclusion: Approximately 1 in 7 children with anaphylaxis experience a biphasic reaction after receiving intramuscular epinephrine. Children with anaphylaxis who exhibit symptomatic resolution four hours following initiation of therapy have a low risk for subsequently developing BPR. Most BPR cases required only one additional dose of IM EPI to effect resolution. The rate of BPR in those receiving IM EPI and a corticosteroid is significantly lower >4 hours vs <4 hours after initiating therapy.